Myosin IIa Promotes Antibody Responses by Regulating B Cell Activation, Acquisition of Antigen, and Proliferation - Hoogeboom, Robbert (Cell Rep, 2018)
B cell responses are regulated by antigen acquisition, processing, and presentation to helper T cells. These functions are thought to depend on contractile activity of non-muscle myosin IIa. Here, we show that B cell-specific deletion of the myosin IIa heavy chain reduced the numbers of bone marrow B cell precursors and splenic marginal zone, peritoneal B1b, and germinal center B cells. In addition, myosin IIa-deficient follicular B cells acquired an activated phenotype and were less efficient in chemokinesis and extraction of membrane-presented antigens. Moreover, myosin IIa was indispensable for cytokinesis. Consequently, mice with myosin IIa-deficient B cells harbored reduced serum immunoglobulin levels and did not mount robust antibody responses when immunized. Altogether, these data indicate that myosin IIa is a negative regulator of B cell activation but a positive regulator of antigen acquisition from antigen-presenting cells and that myosin IIa is essential for B cell development, proliferation, and antibody responses.